Effects of Cultural Practices on Total Phenolics and Vitamin C Content of Organic Table Grapes - Isci, B.; Gokbayrak, Z.; Keskin, N. (South African Journal of Enology and Viticulture, 2016)
The total phenolic and vitamin C contents of organic table grapes were determined by spectrophotometry and HPLC, respectively, after several quality-increasing treatments were applied at véraison for two growing seasons. Cane girdling and cluster-berry thinning resulted in different responses in the cultivars. ‘Red Globe’ generally was found to produce the lowest quantity of total phenolics in the berries, while ‘Trakya Ilkeren’ was the cultivar that accumulated the highest phenolics. Vitamin C accumulation in the berries was also affected by the treatments. The effect of the treatments was inconclusive in ‘Buca Razakısı’. The application of both girdling and thinning caused more accumulation of vitamin C in the ‘Alphonse L.’ and ‘Trakya Ilkeren’ berries.